Comparing Post-Obturation of Apical Microleakage Following the Use of Different Intracanal Chelators - Shantiaee, Yazdan; Dianat, Omid; Mozayeni, Mohammad Ali; Tajedin, Mohammad; Darmiani, Soheila; Kolahi Ahari, Golbarg (Journal of Dental School, 2019)
Objectives: Different chelators may be used during root canal treatment, offering various advantages including lubricant effect inside the canal and smear layer removal. However, chelator residues in narrow root canals can lead to apical microleakage. The aim of this in-vitro study was to compare apical microleakage following the use of three root canal chelators via fluid filtration method in root canals instrumented with ProTaper rotary system. Methods: Sixty-eight distobuccal canals of maxillary first molars were randomly divided into six groups of four experimental (n=15) and a positive and a negative control group (n=4). In groups one to three, RC-Prep, 17% EDTA and Glyde File Prep were used as chelators, respectively and sodium hypochlorite (NaOCl) was used as irrigant in all groups except for group four. In group four, root canals were instrumented without chelators and only saline was used for irrigation. Root canals in all groups were prepared using ProTaper rotary system up to F2 file and filled using cold lateral condensation technique with gutta-percha and AH26 sealer. Apical microleakage was assessed by fluid filtration method. The data were subjected to Kruskal-Wallis test. Results No significant differences were noted among the experimental groups regarding apical microleakage (P>0.05). However, preparations with RC Prep+ NaOCl and Glyde File Prep+ NaOCl yielded the highest and the lowest values of apical microleakage, respectively. Conclusion: Use of different chelators did not cause statistically significant difference in apical microleakage of root canals.